2021
DOI: 10.1007/s11240-021-02103-5
|View full text |Cite
|
Sign up to set email alerts
|

First genome edited poinsettias: targeted mutagenesis of flavonoid 3′-hydroxylase using CRISPR/Cas9 results in a colour shift

Abstract: The CRISPR/Cas9 system is a remarkably promising tool for targeted gene mutagenesis, and becoming ever more popular for modification of ornamental plants. In this study we performed the knockout of flavonoid 3′-hydroxylase (F3′H) with application of CRISPR/Cas9 in the red flowering poinsettia (Euphorbia pulcherrima) cultivar ‘Christmas Eve’, in order to obtain plants with orange bract colour, which accumulate prevalently pelargonidin. F3′H is an enzyme that is necessary for formation of cyanidin type anthocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…These results are consistent with the reports in Chinese Cabbage ( Brassica rapa L. subsp. pekinensis; He et al, 2020a , b , Park et al, 2021 ), O. sativa ( Shih et al, 2008 ), and Paeonia suffruticosa ( Shih et al, 2006 ; Zhang et al, 2020 ; Nitarska et al, 2021 ). In our experiments, FtF3′H1 increased the accumulation of anthocyanin, which may due to the higher expression abundance of FtF3′H1 than FtFLS s or FtF3′H1 has a stronger substrate preference for anthocyanin branch.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the reports in Chinese Cabbage ( Brassica rapa L. subsp. pekinensis; He et al, 2020a , b , Park et al, 2021 ), O. sativa ( Shih et al, 2008 ), and Paeonia suffruticosa ( Shih et al, 2006 ; Zhang et al, 2020 ; Nitarska et al, 2021 ). In our experiments, FtF3′H1 increased the accumulation of anthocyanin, which may due to the higher expression abundance of FtF3′H1 than FtFLS s or FtF3′H1 has a stronger substrate preference for anthocyanin branch.…”
Section: Discussionmentioning
confidence: 99%
“…The disappearance of the vein-associated anthocyanin pattern above the abaxial surface of the flower bud was produced by the CRISPR/Cas9-mediated mutation at DPL , but not corolla tube venation, suggesting that DPL had no influence over corolla tube venation development. Nitarska et al [ 130 ] utilized the CRISPR/Cas9 system to knock out flavonoid 3’-hydroxylase ( F3'H ) from red blooming poinsettias ( Euphorbia pulcherrima ) cultivar ‘Christmas Eve,’ expecting plants with orange bracts and strong pelargonidin accumulation. The enzyme F3'H is required for the synthesis of cyanidin-type anthocyanins, which give poinsettia bracts their red color.…”
Section: Applications Of Crispr/cas9 System In Floriculturementioning
confidence: 99%
“…For this aim, it is necessary to have in vitro plant regeneration and transformation protocols to manipulate the anthocyanin biosynthesis pathway in E . pulcherrima ; fortunately, different authors have reported on these issues ( Geier et al., 1992 ; Clarke et al., 2008 ; Islam et al., 2013 ; Danial and Ibrahim, 2016 );, and even on the possibility of genome editing ( Nitarska et al., 2021 ). Some possibilities and difficulties or limitations to accomplish this goal are discussed here.…”
Section: Introductionmentioning
confidence: 99%